A self-consistent cloud model for brown dwarfs and young giant exoplanets: comparison with photometric and spectroscopic observations - Charnay, B; Bézard, B; Baudino, J-L; Bonnefoy, M; Boccaletti, A; Galicher, R (Institute of Physics, 2018)
We developed a simple, physical and self-consistent cloud model for brown dwarfs and young giant exoplanets. We compared different parametrisations for the cloud particle size, by either fixing particle radii, or fixing the mixing efficiency (parameter fsed) or estimating particle radii from simple microphysics. The cloud scheme with simple microphysics appears as the best parametrisation by successfully reproducing the observed photometry and spectra of brown dwarfs and young giant exoplanets. In particular, it reproduces the L-T transition, due to the condensation of silicate and iron clouds below the visible/near-IR photosphere. It also reproduces the reddening observed for low-gravity objects, due to an increase of cloud optical depth for low gravity. In addition, we found that the cloud greenhouse effect shifts chemical equilibriums, increasing the abundances of species stable at high temperature. This effect should significantly contribute to the strong variation of methane abundance at the L-T transition and to the methane depletion observed on young exoplanets. Finally, we predict the existence of a continuum of brown dwarfs and exoplanets for absolute J magnitude=15-18 and J-K color=0-3, due to the evolution of the L-T transition with gravity. This self-consistent model therefore provides a general framework to understand the effects of clouds and appears well-suited for atmospheric retrievals.